The Impact of Innovative Human Resources Management Practices on Employee Behavior - Pavlova, Oksana (Vilnius University Open Series, 2022)
This paper aims to define the aspects (practices) of innovative human resources management and identify the impact on such behavioral outcomes as employee engagement and organizational commitment at the workplace. Proposed practices for innovative human resources management are: idiosyncratic work arrangements, high performance work systems (HPWS), sustainable workplace, employee autonomy. Review of primary and secondary sources has shown that these variables are related to such positive organizational outcomes as workplace productivity, flexibility, level of innovativeness, resistance to internal and external threats. In addition, it was indicated that intensity of HPWS can lead to a workplace burnout in the long run and it is crucial to understand how HRM practices work and what we should expect. This paper gives an overview of abovementioned HRM practices and what impact they can make on employee behavioral outcomes.